Left atrial stiffness index in the identification of heart failure with preserved ejection fraction - N. E. Shirokov; E. I. Yaroslavskaya; M. D. Kosterin; D. V. Krinochkin; E. A. Gorbatenko; T. N. Enina; N. A. Musikhina (Кардиоваскулярная терапия и профилактика, 2024)
Aim. To study the diagnostic value of the left atrial stiffness index (LASI) of heart failure with preserved ejection fraction (HFpEF) depending assessed by transthoracic echocardiography (TTE) in the diagnosis on diastolic stress test (DST) results.Material and methods. DST was performed in cases of insufficient criteria for increased left ventricular filling pressure assessed by TTE. One hundred patients were examined (52,0% men, 66,1±5,4 years). Patients with a ratio of early transmitral flow velocity to early diastolic mitral annulus velocity (E/e') ratio >15 in DST were included in group I (n=45), patients with E/e' <15 — group II (n=55). The speckle tracking echocardiography was used to assess left atrial reservoir strain (LASr).Results. Significant differences were identified between the groups in sex (40,0% of men in group I and 61,8% in group II, respectively; p=0,044), body mass index (32,9 [29,5;36,0] and 29,6 [27,3;31,8] kg/m2; p=0,001), hypertension stage (2,9±0,3 and 2,5±0,8, p=0,037), the presence of coronary artery disease (88,9 and 67,3%; p=0,016), NYHA heart failure class (2,0±0,4 and 1,5±0,7; p=0,003). TTE revealed significant differences in the left atrium volume index (31,9 [28,5;36,0] and 27,8 [24,1;34,6] ml/m2; p=0,039), E/e' ratio (10,9 [9,7;12,5] and 9,3 [7,4;10,8]; p<0,001), LASr (23,5 [19,3;28,3] and 28,9 [25,6;32,2]%, p<0,001) and LASI (0,46 [0,38;0,56] and 0,30 [0,25;0,39]; p<0,001). According to ROC analysis, the largest area under the curve (AUC), optimal sensitivity and specificity in HFpEF diagnosis were observed in LASI (AUC=0,829, p<0,001; 77,8 and 74,5%, respectively). Lower classification quality was shown by the H2FPEF score (AUC=0,701, p=0,001; 66,7 and 69,1%), while the HFA-PEFF score was not significant in the pretest detection of HFpEF (AUC=0,608, p=0,065; 53,3 and 61,8%).Conclusion. LASI with a cut-off point >0,38 has the greatest ability to detect HFpEF among the possible pretest diagnostic methods.